MODEL KEPEMIMPINAN GEREJA YANG KONTEKSTUAL BERDASARKAN STRUKTUR BUDAYA BATAK MENGGUNAKAN MODEL ANTROPOLOGIS STEPHEN B. BEVANS - Andri Vincent Sinaga; Mangaratua Panjaitan; Marangkup Hutasoit (Phronesis: Jurnal Teologi dan Misi, 2024)
This research proposes a contextualized church leadership model based on Batak cultural structures. The main problem studied is that Western leadership styles still dominate current Batak church leadership and church leadership models that are often considered less responsive (adaptive or contextual) to local culture and socio-cultural values, so they are not entirely contextual and relevant to Batak cultural values. This research uses the anthropological model approach of Stephen B. Bevans anthropological model approach to understand Batak culture deeply and formulate a contextualized church leadership model. This research aims to develop a model of Batak church leadership contextual and relevant to the Batak cultural structure. The research method used is qualitative, with a literature study approach. The results showed that the integration of Batak cultural values such as sahala (authority), Dalihan Na Tolu (DNT), Habonaron Do Bona (HdB), and clan philosophy needs to be the basis for a contextualized Batak church leadership model. The Batak church leadership model should prioritize nurturing, service, respect, and togetherness (solidarity) through these cultural values. Integrating Batak cultural values is essential to forming Batak church leadership that remains rooted in local culture but faithful to the heritage of the Christian faith.